Исследование совмещенного процесса восстановления–карбидизации смеси оксидов WO₃–NiO состава BH8 в промышленной печи - Бондаренко, В.П.; Матвийчук, А.А.; Мошкун, В.Ф.; Сотникова, Л.Л.; Беляева, А.Г. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2006)
It is shown that carbon of a plate takes an active part in the reduction- carburization process. The CO oxide, which is formed by the interaction of WO₃ and NiО with graphite of a plate, diffuses upward in pores of a charge of an oxide mixture and assures carbonization of lower lagers of a sintered compact even to a greater extent than methane of a methane-hydrogen mixture would do. The most rational arrangement of graphite plates in a boot when carrying out the combined reduction-carburization process in an industrial furnace is put forward.